2013
DOI: 10.1037/a0029824
|View full text |Cite
|
Sign up to set email alerts
|

Drinking motives and drinking behavior over time: A full cross-lagged panel study among adults.

Abstract: Drinking motives are among the most proximal factors for drinking behavior and serve as a mechanism through which more distal factors are mediated. However, it is less clear whether drinking motives are precursors of drinking or, in contrast, shaped by previous drinking experiences (reciprocal effects), or both. Moreover, in adults it is unclear whether drinking motives, usually shaped in adolescence, influence each other over time. In this longitudinal study (N = 2440, 47% women, average age 53 years), drinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 28 publications
7
60
1
2
Order By: Relevance
“…The lack of effects of social motives on alcohol use and consequences replicates other cross-sectional work (Magid et al, 2007;Merrill and Read, 2010;Patrick et al, 2011). Other work also has shown nonsignifi cant associations between conformity motives and alcohol use (Crutzen et al, 2013;Magid et al, 2007;Merrill and Read, 2010;Patrick et al, 2011) and suggests that conformity motives may not be particularly relevant for college students (e.g., Karwacki and Bradley, 1996).…”
Section: Other Motivesmentioning
confidence: 71%
See 1 more Smart Citation
“…The lack of effects of social motives on alcohol use and consequences replicates other cross-sectional work (Magid et al, 2007;Merrill and Read, 2010;Patrick et al, 2011). Other work also has shown nonsignifi cant associations between conformity motives and alcohol use (Crutzen et al, 2013;Magid et al, 2007;Merrill and Read, 2010;Patrick et al, 2011) and suggests that conformity motives may not be particularly relevant for college students (e.g., Karwacki and Bradley, 1996).…”
Section: Other Motivesmentioning
confidence: 71%
“…These motive types have less affect regulatory basis and are less frequently related to college drinking (Brown and Finn, 1982;Cooper, 1994;Johnston et al, 2003;Karwacki and Bradley, 1996;MacLean and Lecci, 2000). Nonetheless, research examining the impact of affectrelevant motives typically controls for the shared variance that exists across the range of motives for drinking (Cooper, 1994;Crutzen et al, 2013;Magid et al, 2007;Merrill and Read, 2010), allowing for isolation of the specifi c roles for coping and enhancement motives in drinking behavior.…”
Section: Drinking Motives As Predictors Of Alcohol Use and Consequencesmentioning
confidence: 99%
“…The effect sizes of the cross-lagged associations in previous research were modest (magnitude (ß): 0.10-0.15 for Schelleman-Offermans et al; 21 0.04-0.11 for Crutzen et al 22 ).…”
Section: --Insert Figure 1 About Here --mentioning
confidence: 98%
“…SchellemanOffermans et al 21 reported that higher levels of social motives at baseline predicted an increase in coping motives at follow-up, assuming that younger adolescents might be more sensitive to external social reward than older adolescents. Crutzen et al 22 found that enhancement and coping motives were interlinked (i.e., there was a positive association in both directions between baseline and follow-up), as were social and conformity motives. Additionally, social motives at baseline were positively associated with enhancement motives at follow-up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation